The PI3K/AKT/mTOR signaling pathway is overactivated in primary aldosteronism. - Hengchuan Su; Yanyun Gu; Fengying Li; Qidi Wang; Baoxing Huang; Xiaolong Jin; Guang Ning; Fukang Sun (PLoS ONE, 2013)
BACKGROUND: To date, the available non-invasive remedies for primary aldosteronism are not satisfactory in clinical practice. The phosphoinositide 3-kinase (PI3Ks)/protein kinase B (PKB or AKT)/mammalian target of rapamycin (mTOR) signaling pathway is essential for tumorigenesis and metastasis in many types of human tumors, including renal cancer, adrenal carcinoma and pheochromocytoma. The possibility that this pathway is also necessary for the pathogenesis of primary aldosteronism has not yet been explored. To answer this question, we investigated the activity of the PI3K/AKT/mTOR signaling pathway in normal adrenal glands (NAGs), primary aldosteronism (PA) patients and NCI-H295R cells. METHODOLOGY/PRINCIPAL FINDINGS: Between January 2005 and December 2011, we retrospectively reviewed the records of 45 patients with PA. We compared clinical characteristics (age, gender and biochemical data) and the expression of phospho-AKT (p-AKT), phospho-mTOR (p-mTOR), phospho-S6 (p-S6) and vascular endothelial growth factor (VEGF) by immunohistochemical staining and western blotting, analyzing 30 aldosterone-producing adenomas (APAs), 15 idiopathic hyperaldosteronism (IHA) tissues and 12 NAGs following nephrectomy for renal tumors (control group). Compared with the control group, most of the PA patients presented with polydipsia, polyuria, resistant hypertension, profound hypokalemia, hyperaldosteronemia and decreased plasma renin activity. Compared with normal zona glomerulosa, the levels of p-AKT, p-mTOR, p-S6 and VEGF were significantly upregulated in APA and IHA. No significant differences were found between APA and IHA in the expression of these proteins. Additionally, positive correlations existed between the plasma aldosterone levels and the expression of p-AKT and p-mTOR. In vitro studies showed that mTOR inhibitor rapamycin could inhibit cell proliferation in NCI-H295R cells in a dose- and time-dependent manner. Furthermore, this inhibitor also decreased aldosterone secretion. CONCLUSIONS: Our data suggest that the PI3K/AKT/mTOR signaling pathway, which was overactivated in APA and IHA compared with normal zona glomerulosa, may mediate aldosterone hypersecretion and participate in the development of PA.